Renewable Energy Development in Vietnam - Current Situation and Solutions - Lê Hoàng, Kiệt; Nguyen Van Tuyen (International Journal of Sustainable Applied Sciences, 2024)
Vietnam’s renewable energy sector has witnessed notable advancements in recent years, particularly in wind and solar power generation. However, challenges persist, hindering the sector’s full potential. This study evaluates the current status of renewable energy development in Vietnam from 2015 to the present, identifying existing obstacles and proposing effective solutions. Achievements in harnessing wind, solar, biomass, hydropower, and waste-to-energy sources are highlighted. Challenges such as inadequate grid infrastructure, high initial investment costs, complex administrative procedures, and energy losses are addressed. The paper proposes a comprehensive set of solutions, including infrastructure upgrades, financial incentives, institutional reforms, technology transfers, and research promotion. Implementing these solutions synchronously holds the promise of accelerating Vietnam’s renewable energy development, contributing significantly to sustainable development goals. The findings provide insights for policymakers and stakeholders to enhance the efficiency of green energy deployment in Vietnam.